Fostering Learners' Vocabulary through Jumbled-Letter Game - Nora Fudhla (Edu-Ling: Journal of English Education and Linguistics, 2018)
This article is written based on a research done to solve students’ difficulties in improving their vocabulary skill in MKU classes at Universitas Negeri padang. According to some English teachers and students, teaching vocabulary through memorizing the list was very boring and should be avoided. Besides, it was difficult for the students to write correct spelling for certain vocabularies. To overcome these issues, gamification strategy namely Jumbled-Letter game was applied in an experimental study. The design used in this study was one group pre-test post-test design and the sample was chosen through simple random sampling technique. The data was collected through pre-test and post-test. The data then was analyzed using T Paired test (SPSS 23). Based on the data calculation, the mean score of pre-test was 50.87 and the mean score of post-test was 76.23, and sig. 2 tailed test was < 0.05. Based on T Paired test analysis and interpretation, it was found that the mean score on post-test was increased and the significance score shows that the strategy was significantly effective. Thus, Jumbled-Letter Game was effective to boost learners’ interest and improve their vocabulary mastery.